2017
DOI: 10.1186/s40001-017-0268-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved success rates using videolaryngoscopy in unexperienced users: a randomized crossover study in airway manikins

Abstract: BackgroundVideolaryngoscopy has been proven to be a safe procedure managing difficult airways in the hands of airway specialists. Information about the success rates in unexperienced users of videolaryngoscopy compared to conventional laryngoscopy is sparse. Therefore, we aimed to evaluate if there might be more success in securing an airway if the unexperienced provider is using a videolaryngoscope in simulated airways in a randomized manikin study. Differences between commonly used videolaryngoscopes were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…A comparative mannikin study found that videolaryngoscopy with a Macintosh-like blade performed better than did channelled videolaryngoscopy for the normal airway, whereas the opposite was true for difficult airways [ 32 ]. In a study that used a mannikin with a normal airway, direct laryngoscopy was fastest and also provided a higher first-pass success rate than did the Airtraq™ in the hands of non-experts [ 33 ]. These differences with our results are due to the lower proportion of first-pass success with direct laryngoscopy intubation in our trial compared to previous studies: first-pass success rates ranged from 79 to 100% with direct laryngoscopy, even in the hands of non-experts, [ 32 35 ] compared to 71% in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative mannikin study found that videolaryngoscopy with a Macintosh-like blade performed better than did channelled videolaryngoscopy for the normal airway, whereas the opposite was true for difficult airways [ 32 ]. In a study that used a mannikin with a normal airway, direct laryngoscopy was fastest and also provided a higher first-pass success rate than did the Airtraq™ in the hands of non-experts [ 33 ]. These differences with our results are due to the lower proportion of first-pass success with direct laryngoscopy intubation in our trial compared to previous studies: first-pass success rates ranged from 79 to 100% with direct laryngoscopy, even in the hands of non-experts, [ 32 35 ] compared to 71% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We made this choice, because the proportion of successful first-pass intubations with videolaryngoscopy performed by inexperienced operators on ICU patients was 67.7% in the MACMAN1 trial [ 10 ]. Two of the above-mentioned studies on mannikins used only a normal airway [ 33 , 35 ]. The mean POGO score by direct laryngoscopy ranged from 77 to 80 in the two studies reporting this variable [ 32 , 34 ], both of which simulated difficult airways, compared with 57 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Glidescope ® Go ™ , the Dahlhausen VL and the King Vision ™ with hyperangulated disposable blades, the blade of the I-View ™ one-size single-use VL has a standard Macintosh shape and is significantly longer. In a randomized crossover manikin study, Eismann and colleagues demonstrated, that the hyperangulated blade geometries of VLs provided a better view in difficult airway than the standard geometry of the Macintosh-type blade [ 24 ]. In addition, Schieren and colleagues showed that VLs with hyperangulated blades needed less force for intubation in difficult airways compared to Macintosh shaped laryngoscope blades [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results show that video laryngoscopy was much more effective in achieving successful endotracheal intubation, especially in difficult airways with diminished oral cavity opening or limited neck movement. The video laryngoscopes allowed for much better visualization of the airway than the standard Macintosh laryngoscope [24]. A comparison of the use of several video laryngoscopes by a group of 50 inexperienced in intubation medical students, was also undertaken by Rendeki et al Participants tested a few different devices including King Vision, Airtraq and the Macintosh laryngoscope.…”
Section: Endotracheal Intubation Techniques In Literaturementioning
confidence: 99%